Системний підхід до технічної експлуатації та комплексного розрахунку раціональних конструктивно-технологічних параметрів сортувальних гірок - Огар, О. М. (Eastern-European Journal of Enterprise Technologies, 2009)
Operating scientific approach to the complex calculation and planning of height and longitudinal type of sorting humps is analysed. The necessity of application of systems approach to their technical exploitation and calculation of rational structural-technological parameters is grounded. The model of functioning of sorting hump is resulted